KORUPSI DAN KRISIS KEPERCAYAAN PUBLIC : PERSFEKTIF ETIKA DAN SOSIAL - Dadang Sahroni; Aeni Latifah; Aceng Supyan; Ayu Maryani; Ilmi Siti Najmah Al Fauziyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Corruption is a multidimensional problem that not only harms state finances, but also damages ethical values and public trust in state institutions. This article aims to analyze corruption and the crisis of public trust from an ethical and social perspective. The research uses a literature study method by reviewing relevant books, scientific journals, and official documents. The results of the study show that corruption reflects the moral failure of state administrators, widens social inequality, hinders public services, and weakens the legitimacy of government. Therefore, eradicating corruption cannot be done through law enforcement alone, but also requires strengthening public ethics, transparency, and building a culture of integrity in order to restore public trust.